2010
DOI: 10.1172/jci40266
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation between the transcription factors p63 and IRF6 is essential to prevent cleft palate in mice

Abstract: Cleft palate is a common congenital disorder that affects up to 1 in 2,500 live human births and results in considerable morbidity to affected individuals and their families. The etiology of cleft palate is complex, with both genetic and environmental factors implicated. Mutations in the transcription factor-encoding genes p63 and interferon regulatory factor 6 (IRF6) have individually been identified as causes of cleft palate; however, a relationship between the key transcription factors p63 and IRF6 has not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
191
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(216 citation statements)
references
References 66 publications
23
191
1
Order By: Relevance
“…IRF6 gene expression has been shown previously to be regulated by the binding of the p63 transcription factor to an enhancer element located 9.7 kb upstream of the IRF6 transcription start site (55,56). However, IRF6-binding sites in the IRF6 gene have been identified, leading to the suggestion that IRF6 can also mediate its own expression (8).…”
Section: Discussionmentioning
confidence: 99%
“…IRF6 gene expression has been shown previously to be regulated by the binding of the p63 transcription factor to an enhancer element located 9.7 kb upstream of the IRF6 transcription start site (55,56). However, IRF6-binding sites in the IRF6 gene have been identified, leading to the suggestion that IRF6 can also mediate its own expression (8).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Irf6 siRNA knockdown resulted in downregulation of Irf6 and p21 gene expression and upregulation of p63 gene expression. Previous studies indicate that p63 expression is upregulated in E14.5 Irf6 R84C/R84C palates (Thomason et al, 2010) and siRNA knockdown for Irf6 results in upregulated p63 expression in human keratinocytes (Moretti et al, 2010). Therefore, we investigated whether p63 expression was altered in Irf6 R84C/R84C palates.…”
Section: Research Articlementioning
confidence: 95%
“…We found that p21 expression was restored in E14. Previous studies have demonstrated that IRF6 induces degradation of the p63 isoform ∆Np63 and that this is linked with the pathogenesis of VWS and PPS (Moretti et al, 2010;Thomason et al, 2010). In addition, ∆Np63 represses transcription of p21 in vitro and in vivo (Laurikkala et al, 2006;Welsh and O'Brien, 2009;Westfall et al, 2003).…”
Section: Irf6 Regulates Mee Disappearance Via P21 Expressionmentioning
confidence: 96%
“…In contrast, p63 might indirectly affect RIPK4 expression via its effect on IRF6 expression. 38 This increase in IRF6 may then lead to p63 degradation in keratinocytes, thereby restricting the proliferative potential and promoting keratinocyte differentiation. 39 Our data do not exclude that under certain conditions an interplay between IRF6 and p63 directly enhances RIPK4 promoter activity.…”
Section: G H and I)mentioning
confidence: 99%